Randang Lokan Processing in Nagari Muaro Sakai Inderapura Pesisir Selatan Regency - Andhini Azzahra; Elida; Kasmita; Lucy Fridayati (Siber Journal of Advanced Multidisciplinary, 2026)
This study aims to describe the processing of Randang Lokan in Nagari Muaro Sakai Inderapura, South Coast Regency which includes the composition of ingredients, spices, equipment, and processing processes. This study uses a descriptive method with a qualitative approach. Research informants were determined using purposive sampling techniques, while data collection was carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data was tested using source triangulation and triangulation techniques. The results of the study showed that the main ingredients of Randang Lokan consisted of lokan, coconut milk, and ferns, while the additional ingredients used by some of the informants were leman tapak leaves and roasted coconut. The spices used include onion, garlic, red chili, ginger, galangal, lemongrass, turmeric leaves, lime leaves, bay leaves, and salt. The equipment used is still dominated by traditional equipment, such as lado, gadang cauldrons, wooden stoves, coconut grating machines, and wood mixer spoons. The processing process starts from cleaning and boiling lokan, making coconut milk, refining spices, cooking coconut milk to removing oil, adding spices, lokan, and ferns, then cooking until dry and blackish-brown. The difference found lies only in the use of additives, while the basic processing techniques are relatively the same for each informant. Thus, the processing of Randang Lokan in Nagari Muaro Sakai Inderapura still maintains traditional techniques that have been passed down from generation to generation and is a form of preserving the region's culinary heritage.